A modified positive electrode lithium supplement material, a positive electrode of a lithium ion battery and a lithium ion battery

By covering polysiloxane compounds on the surface of lithium-rich oxide particles, the problems of poor stability and poor processing performance of existing positive electrode lithium supplement materials are solved, and the battery capacity is improved and the slurry gel problem is improved.

CN115911366BActive Publication Date: 2025-04-22HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310111395.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2025-04-22
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

The existing positive electrode lithium supplement materials have problems such as poor stability, poor processing performance, low ionic conductivity and large polarization, which limits their application in lithium-ion batteries.

Method used

By covering polysiloxane compounds on the surface of lithium-rich oxide particles, a cladding layer is formed, structural stability is improved, surface residual alkali is reduced, and a 3D high-efficiency Li+ transmission network is constructed.

Benefits of technology

It effectively improves the slurry gel problem, extends the coating window period, improves battery capacity, and improves the processing and electrochemical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004076936790000011
    Figure HDA0004076936790000011
Patent Text Reader

Abstract

The present invention discloses a modified positive electrode lithium supplement material, a lithium ion battery positive electrode and a lithium ion battery. The modified positive electrode lithium supplement material of the present invention comprises lithium-rich oxide particles and a coating layer made of a polysiloxane compound coated on the surface of the lithium-rich oxide particles; the lithium-rich oxide particles are Li 5 FeO 4 , Li 6 CoO 4 and Li 2 NiO 2 The polysiloxane compound is selected from any one of polydimethylsiloxane, polymethylphenylsiloxane and polyphenylmethylsiloxane; wherein the polysiloxane compound is cross-linked between the lithium-rich oxide particles. The present invention uniformly coats the polyalkylene oxide on the surface of the lithium-rich oxide particles and forms effective cross-links between the particles to construct a 3D efficient Li + Transmission network, improves capacity; effectively isolates lithium-rich oxide from moisture in the air, reduces surface residual alkali, improves its structural stability, significantly extends the coating window period during processing, and effectively improves the slurry gel problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium replenishment of lithium ion battery positive electrode, and in particular to a modified positive electrode lithium replenishment material, a lithium ion battery positive electrode and a lithium ion battery. Background Art

[0002] In recent years, the rapid development of portable electronic products, new energy vehicles, smart grids, distributed energy storage, and the Internet of Things has put forward higher and higher requirements for the performance of lithium-ion batteries, among which the improvement of battery energy density is the most urgent. As an important means to improve battery energy density, lithium-ion battery lithium replenishment technology has gradually become a hot research direction. Most of the existing high-specific capacity electrode materials will lose a large amount of active lithium due to the formation of SEI film during the first charge and discharge, resulting in a low coulombic efficiency (ICE) of the first cycle, thereby reducing the capacity and energy density of lithium-ion batteries. The irreversible capacity loss of the most widely used graphite negative electrode is greater than 6%, while for silicon-based and tin-based alloy negative electrodes with high specific capacity, the irreversible capacity loss is even as high as 10% to 20%. By cooperating with lithium replenishment technology, the active lithium lost in the first cycle can be compensated, the short board of low first efficiency can be improved, and its high capacity advantage can be fully utilized to achieve the effect of improving the energy density of lithium-ion batteries.

[0003] As an important type of positive electrode lithium supplement additive, lithium-rich oxide system has attracted extensive attention from researchers due to its good compatibility with battery systems, low production cost, non-toxicity and high lithium supplement capacity. However, existing studies have shown that lithium-rich oxide materials are extremely sensitive to the environment (H2O and CO2) and have low intrinsic conductivity, which makes industrialization and application extremely difficult, limiting its market promotion. The current domestic and foreign markets are still in the application development and verification stage of lithium-rich oxide products, with problems such as poor production stability and processing difficulties, and there is no large-scale production and application. At the same time, due to the presence of a large amount of free Li on the surface + This results in a high level of residual alkali, which when added to the positive electrode usually causes the slurry to gel and become unable to be coated, greatly limiting the promotion and application of lithium replenishment technology. Summary of the invention

[0004] In view of the problems of poor stability, poor processing performance, low ion conductivity, large polarization, etc. of the existing positive electrode lithium replenishing materials, the purpose of the present invention is to provide a modified positive electrode lithium replenishing material, a lithium ion battery positive electrode and a lithium ion battery. The modified positive electrode lithium replenishing material can not only reduce the surface residual alkali and improve its structural stability by coating the surface of the lithium-rich oxide particles with a polysiloxane compound, so that the coating window period during processing is significantly extended, the slurry gel problem is effectively improved, and the battery capacity can be increased.

[0005] In a first aspect, the present invention provides a modified positive electrode lithium supplement material, which comprises lithium-rich oxide particles and a coating layer made of a polysiloxane compound coated outside the lithium-rich oxide particles;

[0006] The lithium-rich oxide particles are any one of Li5FeO4, Li6CoO4 and Li2NiO2;

[0007] The polysiloxane compound is selected from any one of polydimethylsiloxane, polymethylphenylsiloxane and polyphenylmethylsiloxane;

[0008] Wherein, the polysiloxane compound is cross-linked between the lithium-rich oxide particles.

[0009] In the modified positive electrode lithium supplement material, the mass ratio of the polysiloxane compound to the lithium-rich oxide particles may be (0.01-0.10):1, specifically (0.02-0.10):1, (0.04-0.10):1, (0.02-0.04):1, 0.10:1, 0.04:1 or 0.02:1;

[0010] The coating layer may have a thickness of 0.1 to 1.0 μm, specifically 0.1 to 0.6 μm, 0.1 to 0.5 μm, 0.1 to 0.2 μm, 0.2 to 0.6 μm, 0.2 to 0.5 μm, 0.5 to 0.6 μm, 0.5 μm, 0.1 μm, 0.2 μm or 0.6 μm.

[0011] In the above-mentioned modified positive electrode lithium-supplementing material, the average diameter of the lithium-rich oxide particles may be 0.5-10 μm, specifically 1-8 μm, 1-5 μm, 1-3 μm, 1-2 μm, 2-8 μm, 2-5 μm, 2-3 μm, 3-8 μm, 3-5 μm, 5-8 μm, 5 μm, 3 μm, 2 μm, 8 μm or 1 μm.

[0012] In the modified positive electrode lithium supplement material, the polydimethylsiloxane (molecular formula (C2H6OSi) n ) may have a molecular weight of 1000 to 5000, specifically 2500;

[0013] The polymethylphenylsiloxane (molecular formula is (C7H8OSi) n ) has a molecular weight of 1000 to 3000, specifically 2700;

[0014] The polyphenylmethylsiloxane (molecular formula (C6H5(CH3)SiO2) n ) has a molecular weight of 2000 to 5000, and specifically may be 2500.

[0015] In a second aspect, the present invention provides a method for preparing the modified positive electrode lithium supplement material as described in any one of the above, comprising the following steps:

[0016] S1, placing the lithium-rich oxide particles in an organic solvent for ultrasonic treatment, and drying after the ultrasonic treatment;

[0017] S2. Using the polysiloxane compound as a deposition material, under the protection of an inert atmosphere, chemical vapor deposition is performed on the lithium-rich oxide particles treated in step S1 to form the coating layer, thereby obtaining the modified positive electrode lithium supplement material.

[0018] In the above preparation method, the organic solvent is any one of anhydrous ethanol, anhydrous methanol, isopropanol, acetonitrile and acetone;

[0019] The power of the ultrasonic treatment may be 80-200 W, specifically 80-150 W, 80-100 W, 100-150 W, 100-200 W, 150-200 W, 80 W, 200 W, 100 W or 150 W, and the time may be 15-60 min, specifically 15-50 min, 15-30 min, 30-50 min, 30-60 min, 50-60 min, 60 min, 15 min, 30 min or 50 min;

[0020] The drying temperature can be 60-120°C, specifically 80-120°C, 80°C or 120°C; the drying time can be 8-24h, specifically 8-16h, 16-24h, 8h, 16h, 24h; the vacuum degree is ≤-0.02MPa, specifically -0.09MPa to -0.02MPa, -0.09MPa to -0.05MPa, -0.05MPa to -0.02MPa, -0.05MPa, -0.09MPa or -0.02MPa.

[0021] In the above preparation method, the temperature of the chemical vapor deposition can be 200-300°C, specifically 200-250°C, 250-300°C, 300°C, 200°C or 250°C; the time can be 0.5-5h, specifically 1-2h, 2h or 1h.

[0022] In the above preparation method, the inert gas may be nitrogen or argon.

[0023] In a third aspect, the present invention provides the use of the modified positive electrode lithium supplement material in any one of the following 1)-3):

[0024] 1) Reduce the residual alkali LiOH content on the surface;

[0025] 2) Increase the battery's initial charge capacity;

[0026] 3) Prolong the gel time of slurry.

[0027] In a fourth aspect, the present invention provides a lithium-ion battery positive electrode, which comprises any of the modified positive electrode lithium-supplementing materials described above.

[0028] In at least one embodiment of the present invention, the positive electrode of the lithium-ion battery is composed of the modified positive electrode lithium supplement material, carbon black and PVDF in a mass ratio of 8:1:1.

[0029] In at least one other embodiment of the present invention, the lithium-ion battery positive electrode is composed of a mixture of the modified positive electrode lithium supplement material and lithium iron phosphate, carbon black and PVDF in a mass ratio of 8:1:1, and the mass percentage of the modified positive electrode lithium supplement material in the mixture of the modified positive electrode lithium supplement material and lithium iron phosphate is 5%.

[0030] In a fifth aspect, the present invention provides a lithium-ion battery, which comprises any one of the modified positive electrode lithium-supplementing materials or the lithium-ion battery positive electrode described above.

[0031] In at least one embodiment of the present invention, the lithium-ion battery is a button battery, the battery negative electrode is a metal lithium sheet, the separator is a polypropylene microporous membrane, the electrolyte is a 1 mol / L LiPF6 solution, and the electrolyte solvent is EC, DMC and EMC in a volume ratio of 1:1:1.

[0032] The beneficial effects of the present invention are as follows: the present invention designs a surface coating layer to coat the lithium-rich oxide of the positive electrode lithium supplement material, (1) polyalkylene oxide is uniformly coated on the surface of the lithium-rich oxide particles by chemical vapor deposition and effective cross-linking is formed between the particles to construct a 3D high-efficiency Li + transmission network, improving capacity; (2) effectively isolating lithium-rich oxide from moisture in the air, reducing surface residual alkali, improving its structural stability, significantly extending the coating window period during processing, and effectively improving the slurry gel problem. (3) Due to the hydrophobic and oleophilic properties of the coating layer, the lithium supplement additive has an excellent match with traditional oil-based adhesives, and the contact with the positive electrode material is more uniform and close, which has a significant effect on improving battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The SEM images of Example 1 (a) and Comparative Example 3 (b) are shown. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0035] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0036] Example 1

[0037] Lithium iron-rich lithium oxide (Li5FeO4) was soaked in anhydrous ethanol and placed in an ultrasonic cleaner for ultrasonic treatment for 60 minutes. The ultrasonic power used was 80W, which fully washed away the surface alkaline impurities and formed a rough layer on the surface of Li5FeO4. It was placed in a vacuum drying oven at 80°C (vacuum degree -0.05MPa) and baked for 8 hours to obtain surface-treated Li5FeO4 particles.

[0038] 5 g of the purified Li5FeO4 particles (average diameter of 5 μm) and 0.5 g of polydimethylsiloxane (molecular weight of 2500) were placed in a high-temperature resistant sealable container, nitrogen was introduced, and high-temperature treatment was performed at 300°C for 2 h, so that polydimethylsiloxane slowly self-assembled on the surface of Li5FeO4 and deposited to form a coated modified Li5FeO4 composite material with a coating layer thickness of 0.5 μm.

[0039] The prepared coated modified Li5FeO4 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured a voltage range of 2V-4.5V, and a charge and discharge current of 0.05C.

[0040] The prepared coated modified Li5FeO4 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0041] Example 2

[0042] Lithium iron-rich lithium oxide (Li5FeO4) was immersed in anhydrous methanol and placed in an ultrasonic cleaning machine for ultrasonic treatment for 15 minutes. The ultrasonic power used was 200W, which fully washed away the surface alkaline impurities and formed a rough layer on the surface of Li5FeO4. It was placed in a 120°C vacuum drying oven (vacuum degree -0.09MPa) and baked for 16 hours to obtain surface-treated Li5FeO4 particles.

[0043] 5 g of the purified Li5FeO4 particles (average diameter of 3 μm) and 0.2 g of polymethylphenylsiloxane (molecular weight of 2700) were placed in a high-temperature resistant sealable container, nitrogen was introduced, and high-temperature treatment was performed at 200°C for 1 hour, so that the polymethylphenylsiloxane slowly self-assembled on the surface of Li5FeO4 and deposited to form a coated modified Li5FeO4 composite material with a coating layer thickness of 0.1 μm.

[0044] The prepared coated modified Li5FeO4 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured a voltage range of 2V-4.5V, and a charge and discharge current of 0.05C.

[0045] The prepared coated modified Li5FeO4 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0046] Example 3

[0047] Lithium nickel-rich lithium oxide (Li2NiO2) was soaked in acetonitrile and placed in an ultrasonic cleaning machine for ultrasonic treatment for 30 minutes. The ultrasonic power used was 200W, which fully washed away the surface alkaline impurities and formed a rough layer on the surface of Li2NiO2. It was placed in a 120°C vacuum drying oven (vacuum degree -0.09MPa) and baked for 24 hours to obtain surface-treated Li2NiO2 particles.

[0048] 5 g of the purified Li2NiO2 particles (average diameter of 2 μm) and 0.1 g of polyphenylmethylsiloxane (molecular weight of 2500) were placed in a high-temperature resistant sealable container, argon gas was introduced, and high-temperature treatment was carried out at 250°C for 1 hour, so that the polyphenylmethylsiloxane slowly self-assembled on the surface of Li2NiO2 and deposited to form a coated modified Li2NiO2 composite material with a coating layer thickness of 0.2 μm.

[0049] The prepared super-hydrophobic layer-coated Li2NiO2 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of a lithium-ion battery. A button cell model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button cell measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0050] The prepared coated modified Li2NiO2 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of lithium-ion battery, and button batteries of model CR2032 were assembled in a glove box filled with argon. The negative electrode of the battery is a metal lithium sheet, the diaphragm is a polypropylene microporous membrane, the electrolyte is a 1mol / L LiPF6 solution, and the electrolyte solvent is EC:DMC:EMC=1:1:1(v / v / v). The button battery measurement voltage range is 2V-4.5V, and the charge and discharge current is 0.05C.

[0051] Example 4

[0052] Lithium nickel-rich lithium oxide (Li2NiO2) was soaked in isopropanol and placed in an ultrasonic cleaner for ultrasonic treatment for 30 minutes. The ultrasonic power used was 100W, which fully washed away the surface alkaline impurities and formed a rough layer on the surface of Li2NiO2. It was placed in a vacuum drying oven at 80°C (vacuum degree -0.09MPa) and baked for 24 hours to obtain surface-treated Li2NiO2 particles.

[0053] 5 g of the purified Li2NiO2 particles (average diameter of 8 μm) and 0.5 g of polymethylphenylsiloxane (molecular weight of 2700) were placed in a high-temperature resistant sealable container, argon gas was introduced, and the container was treated at 250°C for 1 hour, so that the polymethylphenylsiloxane slowly self-assembled on the surface of Li2NiO2 and deposited to form a coated modified Li2NiO2 composite material with a coating layer thickness of 0.6 μm.

[0054] The prepared coated modified Li2NiO2 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0055] The prepared coated modified Li2NiO2 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of lithium-ion battery, and button batteries of model CR2032 were assembled in a glove box filled with argon. The negative electrode of the battery is a metal lithium sheet, the diaphragm is a polypropylene microporous membrane, the electrolyte is a 1mol / L LiPF6 solution, and the electrolyte solvent is EC:DMC:EMC=1:1:1(v / v / v). The button battery measurement voltage range is 2V-4.5V, and the charge and discharge current is 0.05C.

[0056] Example 5

[0057] Lithium-rich cobalt oxide (Li6CoO4) was soaked in isopropanol and placed in an ultrasonic cleaner for ultrasonic treatment for 50 minutes. The ultrasonic power used was 150W, which fully washed away the surface alkaline impurities and formed a rough layer on the surface of Li6CoO4. It was placed in a 120°C vacuum drying oven (vacuum degree -0.02MPa) and baked for 24 hours to obtain surface-treated Li6CoO4 particles.

[0058] 5 g of the purified Li6CoO4 particles (average diameter of 1 μm) and 0.5 g of polymethylphenylsiloxane (molecular weight of 2700) were placed in a high-temperature resistant sealable container, argon gas was introduced, and high-temperature treatment was carried out at 250°C for 2 hours, so that the polyphenylmethylsiloxane slowly self-assembled on the surface of Li6CoO4 and deposited to form a coated modified Li6CoO4 composite material with a coating layer thickness of 0.1 μm.

[0059] The prepared coated modified Li6CoO4 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0060] The prepared coated modified Li6CoO4 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery is a metal lithium sheet, the diaphragm is a polypropylene microporous membrane, the electrolyte is a 1mol / L LiPF6 solution, and the electrolyte solvent is EC:DMC:EMC=1:1:1(v / v / v). The button battery measurement voltage range is 2V-4.5V, and the charge and discharge current is 0.05C.

[0061] Comparative Example 1

[0062] 5 g of Li5FeO4 particles (average diameter of 5 μm) and 0.5 g of polydimethylsiloxane (molecular weight of 2500) were placed in a high-temperature resistant sealable container, nitrogen was introduced, and high-temperature treatment was performed at 300°C for 2 h, so that polydimethylsiloxane slowly self-assembled on the surface of Li5FeO4 and deposited to form a Li5FeO4 composite material.

[0063] In this comparative example, the surface of Li5FeO4 is not treated and a uniform and complete coating layer cannot be formed.

[0064] The prepared Li5FeO4 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0065] The prepared Li5FeO4 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0066] Comparative Example 2

[0067] Lithium iron-rich lithium oxide (Li5FeO4) was soaked in anhydrous ethanol for 60 minutes, and then placed in a vacuum drying oven at 80°C (vacuum degree -0.05MPa) and baked for 8 hours to obtain surface-treated Li5FeO4 particles.

[0068] 5 g of the purified Li5FeO4 particles (average diameter of 5 μm) and 0.5 g of polydimethylsiloxane (molecular weight of 2500) were placed in a high-temperature resistant sealable container, nitrogen was introduced, and high-temperature treatment was performed at 300°C for 2 h, so that polydimethylsiloxane slowly self-assembled on the surface of Li5FeO4 and deposited to form a Li5FeO4 composite material with a coating layer thickness of 0.5 μm.

[0069] The prepared Li5FeO4 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0070] The prepared Li5FeO4 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0071] Comparative Example 3

[0072] Lithium iron-rich lithium oxide (Li5FeO4) was soaked in anhydrous ethanol and placed in an ultrasonic cleaning machine for ultrasonic treatment for 60 minutes. The ultrasonic power used was 80W, which fully washed away the surface alkaline impurities and formed a rough layer on the surface of Li5FeO4. It was placed in a vacuum drying oven at 80°C (vacuum degree -0.05MPa) and baked for 8 hours to obtain surface-treated Li5FeO4 particles.

[0073] 5 g of the purified Li5FeO4 particles (average diameter of 5 μm) were placed in a high-temperature resistant sealable container, nitrogen was introduced, and high-temperature treatment was performed at 300° C. for 2 h.

[0074] The prepared Li5FeO4 material was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0075] The prepared Li5FeO4 material was mixed with lithium iron phosphate positive electrode material in a mass ratio of 5:95, and then the mixture was mixed and ground with carbon black and PVDF in a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of the lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, the electrolyte was a 1 mol / L LiPF6 solution, and the electrolyte solvent was EC:DMC:EMC=1:1:1(v / v / v). The button battery measured voltage range was 2V-4.5V, and the charge and discharge current was 0.05C.

[0076] Comparative Example 4

[0077] Disperse 0.5 g of polydimethylsiloxane (molecular weight 2500) in 10 mL of anhydrous ethanol, add 5 g of Li5FeO4 powder to the mixture, stir thoroughly for 5 h until uniform, filter and wash with 10 mL of anhydrous ethanol, then heat at 60 ° C to evaporate the solvent, and finally put it in a vacuum oven at 100 ° C to dry for 12 h to remove the residual solvent to obtain a composite material.

[0078] The SEM images of Example 1 and Comparative Example 3 are shown in Figure 1 ,from Figure 1 It can be seen that compared with Comparative Example 3, the surface roughness of Example 1 increases after being coated with polysiloxane, and the degree of crosslinking between particles increases significantly.

[0079] The physical, chemical and electrical properties of the positive electrode lithium supplement materials prepared in the above-mentioned Experimental Examples 1-5 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.

[0080] The test method is as follows:

[0081] Residual alkali LiOH test method: accurately weigh 0.3g sample into a 100ml clean and dry washing bottle, add 100ml ethanol to the washing bottle and stir for 5min. After stirring, vacuum filter and collect the filtrate into a 100ml volumetric flask. Transfer 40ml of the filtrate into the titration cup; titrate with 0.01M HCl standard solution to obtain the titration curve, and record the volume V1 of the hydrochloric acid standard solution consumed in this process. At the same time, analyze the method blank, the volume V0 of hydrochloric acid consumed at the end point, and the LiOH content = 23.94×0.01×(V1-V0) / 120.

[0082] Gel time determination method: The prepared Li5FeO4 material is mixed with carbon black and PVDF in a mass ratio of 8:1:1, wherein PVDF is a 5% mass concentration of PVDF dispersed in NMP to form a glue. The mixture is placed in a slurry mixer and dispersed at 1950rmp for 10 minutes before being taken out. The timing starts from the time of taking out and stops when the glue completely solidifies into a jelly-like state without fluidity. This duration is the slurry gel time. The experimental test conditions are a temperature of 25°C and a dew point of -30°C.

[0083] Table 1. Test results of positive electrode lithium supplement materials

[0084] sample Residual alkali (LiOH) First charge capacity of positive electrode lithium supplement material Slurry gel time Example 1 220ppm 622.3mAh / g 400min Example 2 312ppm 608.9mAh / g 315min Example 3 488ppm 386.0mAh / g 205min Example 4 431ppm 365.6mAh / g 200min Example 5 189ppm 855.7mAh / g 465min Comparative Example 1 1165ppm 597.7mAh / g 12min Comparative Example 2 976ppm 567.9mAh / g 36min Comparative Example 3 1808ppm 564.8mAh / g 4min Comparative Example 4 877ppm 467.9mAh / g 40min

[0085] As can be seen from Table 1, compared with Comparative Examples 1-4, the residual alkali LiOH content of Examples 1-5 is significantly reduced. Compared with Comparative Examples 1-4, the first charge capacity of Li5FeO4 materials after coating modification is improved. Compared with Comparative Examples 1-4, the slurry gel time of Examples 1-5 is greatly extended, indicating that the polysiloxane coating forms an efficient Li + The transmission network can effectively improve capacity utilization, and the residual alkali value is reduced after surface coating, and the gel time of the slurry is significantly prolonged.

[0086] In order to further evaluate the lithium replenishment effect of the positive electrode lithium replenishment material prepared by this method, it was added to the lithium iron phosphate positive electrode material at a mass ratio of 5%, and mixed and coated to make a buckle battery. Table 2 shows the performance of the electrical performance of the lithium replenishment material added to the positive electrode material. The test method is the same as above.

[0087] Table 2. Test results of 5% lithium supplement material + lithium iron phosphate

[0088] sample 5% lithium supplement material + lithium iron phosphate first charge capacity Slurry gel time Example 1 183.9mAh / g 585min Example 2 180.7mAh / g 470min Example 3 172.5mAh / g 335min Example 4 171.2mAh / g 335min Example 5 191.3mAh / g 525min Comparative Example 1 173.1mAh / g 20min Comparative Example 2 174.6mAh / g 30min Comparative Example 3 173.6mAh / g 8min Comparative Example 4 171.0mAh / g 23min

[0089] As can be seen from Table 1, compared with Comparative Examples 1-4, the slurry gel time of Examples 1 and 2 is greatly improved, and the first charge capacity is also improved, indicating that polysiloxane coating of the lithium supplement material is beneficial to promoting the uniform dispersion of the material in the slurry and strengthening the effect.

[0090] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements of the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing a modified positive electrode lithium supplement material, characterized in that: The modified positive electrode lithium supplement material comprises lithium-rich oxide particles and a coating layer made of a polysiloxane compound coated on the surface of the lithium-rich oxide particles; The lithium-rich oxide particles are any one of Li5FeO4, Li6CoO4 and Li2NiO2; The polysiloxane compound is selected from any one of polydimethylsiloxane, polymethylphenylsiloxane and polyphenylmethylsiloxane; Wherein, the polysiloxane compound is cross-linked between the lithium-rich oxide particles; The preparation method comprises the following steps: S1, placing the lithium-rich oxide particles in an organic solvent for ultrasonic treatment, and drying after the ultrasonic treatment; S2. Using the polysiloxane compound as a deposition material, under the protection of an inert atmosphere, chemical vapor deposition is performed on the lithium-rich oxide particles treated in step S1 to form the coating layer, thereby obtaining the modified positive electrode lithium supplement material.

2. The method for preparing the modified positive electrode lithium supplement material according to claim 1, characterized in that: The mass ratio of the polysiloxane compound to the lithium-rich oxide particles is (0.01-0.10):1; The coating layer has a thickness of 0.1 to 1.0 μm.

3. The method for preparing the modified positive electrode lithium supplement material according to claim 1 or 2, characterized in that: The average diameter of the lithium-rich oxide particles is 0.5-10 μm.

4. The method for preparing the modified positive electrode lithium supplement material according to claim 1 or 2, characterized in that: The molecular weight of the polydimethylsiloxane is 1000 to 5000; The molecular weight of the polymethylphenylsiloxane is 1000 to 3000; The molecular weight of the polyphenylmethylsiloxane is 2000-5000.

5. The method for preparing the modified positive electrode lithium supplement material according to claim 1, characterized in that: The organic solvent is any one of anhydrous ethanol, anhydrous methanol, isopropanol, acetonitrile and acetone; The power of the ultrasonic treatment is 80 to 200 W, and the time is 15 to 60 minutes; The drying temperature is 60-120° C., the drying time is 8-24 hours, and the vacuum degree is ≤-0.02 MPa.

6. The method for preparing the modified positive electrode lithium supplement material according to claim 1, characterized in that: The temperature of the chemical vapor deposition is 200-300° C., and the time is 0.5-5 hours.

Citation Information

Patent Citations

  • Composite lithium supplement additive and preparation method and application thereof

    CN113036106A

  • Method for modifying electrode material by crosslinking and self-assembling polysiloxane

    CN115172715A